IMPLEMENTATION OF THE BOARDING SCHOOL PROGRAMME IN SHAPING THE MORALS OF BIMA CITY STUDENTS - Adam, Adam; Ruslan, Ruslan; Kaharuddin, Kaharuddin (Fakultas Tarbiyah, IAIN Fattahul Muluk Papua, 2024)
This study aims to describe how the implementation of the boarding school program in shaping the morals of Bima City students and analyse the supporting and inhibiting factors in its implementation. This research is a descriptive qualitative research. Primary data is taken from coaches and students while secondary data is in the form of references used. Data collection techniques using observation, interviews, and documentation. To analyse the data through three stages, namely data reduction, data presentation and conclusion drawing. Testing the credibility of data with member check, croos chek, and triangulation. The results showed that the implementation of the boarding school programme in shaping the morals of Bima City students through several activities, among others: Habituation of compulsory and sunnah worship (five daily prayers, tahajjud prayers, and sunnah fasting on Monday and Thursday), habituation of morning and evening dhikr, santri tausiah activities, boarding school programme evaluation activities, reinforcement with moral learning, tahfidzul Qur'an. The supporting factors are the full support of the Madrasah, adequate facilities and infrastructure, and sufficient coaches. For the obstacles faced there is nothing too significant, but it becomes a challenge for the coach such as students have different backgrounds. This is a step for the coach to continue learning to respond to his students.